Using email reminders to engage physicians in an Internet-based CME intervention - Abdolrasulnia, Maziar (BioMed Central, 2004)
BACKGROUND: Engaging practicing physicians in educational strategies that reinforce guideline adoption and improve the quality of healthcare may be difficult. Push technologies such as email offer new opportunities to engage physicians in online educational reinforcing strategies. The objectives are to investigate 1) the effectiveness of email announcements in engaging recruited community-based primary care physicians in an online guideline reinforcement strategy designed to promote Chlamydia screening, 2) the characteristics of physicians who respond to email announcements, as well as 3) how quickly and when they respond to email announcements. METHODS: Over a 45-week period, 445 recruited physicians received up to 33 email contacts announcing and reminding them of an online women's health guideline reinforcing CME activity. Participation was defined as physician log-on at least once to the website. Data were analyzed to determine participation, to compare characteristics of participants with recruited physicians who did not participate, and to determine at what point and when participants logged on. RESULTS: Of 445 recruited physicians with accurate email addresses, 47.2% logged on and completed at least one module. There were no significant differences by age, race, or specialty between participants and non-participants. Female physicians, US medical graduates and MDs had higher participation rates than male physicians, international medical graduates and DOs. Physicians with higher baseline screening rates were significantly more likely to log on to the course. The first 10 emails were the most effective in engaging community-based physicians to complete the intervention. Physicians were more likely to log on in the afternoon and evening and on Monday or Thursday. CONCLUSIONS: Email course reminders may enhance recruitment of physicians to interventions designed to reinforce guideline adoption; physicians' response to email reminders may vary by gender, degree, and country of medical training. Repetition of email communications contributes to physician online participation.